The Effects of Problem-Based Learning and Web-Based Learning on School Administrators’ Decision-Making Styles and Competencies - Karabatak, Songül (My University, 2020)
In this study, the effects of problem-based learning and web-based learning on school administrators’ decision-making styles and competencies were investigated. The mixed-method was performed in the study. In the qualitative dimension, a semi-structured interview technique was used. The quantitative dimension was conducted experimentally and Melbourne Decision-making Questionnaire II was used to collect data. The participants were determined by purposive sampling method. One experimental and one control group were identified in the study and 31 participants were included in each group. Findings indicated that the school administrator training program, in which web-based learning and problem-based learning are used together, had a significantly positive effect on the participants’ decision-making styles. In addition, the training program also increased the decision-making competencies of the school administrators such as compromise with others, evaluation of the result of decisions, control and choice of decision, creative problem-solving, being consistent in decisions, effective and correct decision-making, and providing credibility in decision-making. At the end of the study, some suggestions were made to the researchers and educators.
Keywords: Eğitim; Eğitim Araştırmaları; Kamu Yönetimi